THE MANAGEMENT OF SPEAKING INSTRUCTION AT SMA MODAL BANGSA, ACEH PROVICE - Sariakin Sariakin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The purposes of this research are (1) to find out how the teachers make preparation for managing speaking instruction, (2) to find out how English teachers design classroom management for teaching speaking skill, and (3) to find out how the teachers make as assessment of speaking instruction. The subject of this research is all teachers of SMA Modal Bangsa who teach English especially speaking skill and there are four subjects. The design used in this research is descriptive research and it belongs to qualitative research. Thus, this research is conducted to analyze a management of speaking instruction at the school. Data needed were gotten through observation, interview, and documentation. Data gotten are analyzed by narration procedure and discussing. The result of the research shows that the teachers prepare classroom management of reading instruction by preparing lesson plan, materials, and conducive environment for instruction process. Next, the teachers usually use six methods namely: asking opinion, debate, roll play, discussion, problem solving and speech in managing speaking instruction. Furthermore, the teachers evaluate the students in teaching English speaking skill in two kinds of tests namely on going process test and final test. The tests of English speaking skill were orally. The tests are parted into six categories, there are: fluency of speaking, pronunciation, grammar, sound gesture and content